Education, Social Equality and Economic Growth: A View of the Landscape - Thorvaldur Gylfason; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2003)
Education has been one of the key determinants of economic growth around the world since 1965. In this paper, we discuss three different measures of education, and consider their relationship to the distribution of income as measured by the Gini coefficient as well as to economic growth across countries. The three measures are: (a) gross secondary-school enrolment, (b) public expenditure on education relative to national income and (c) expected years of schooling for girls. We show that all three measures of education are directly related to income equality across countries. In a sample of 87 countries at all income levels, we also find that more and better education appears to encourage economic growth directly as well as indirectly through increased social equality and cohesion. Our regression results survive the introduction of regional dummy variables for Africa, Asia and Central and South America. We argue that the empirical relationship between education, on the one hand, and growth and equality, on the other hand, can help account for the positive correlation between the two latter variables that has been documented in the literature.
Keywords: 330